Improvement of recovery cycle of cryopreserved potato shoot tips – Small changes, but huge impact - Vollmer, R.; Espirilla, J.; Villagaray, R.; Castro, M.; Cardenas, J.; Pineda, S.; Azevedo, V.C.R. (Elsevier, 2022)
Improvement and optimization of cryopreservation protocols for its reliable large-scale application is a time-consuming process. The development of robust and efficient protocols implicates the assessment of a high number of diverse genotypes before results can be extrapolated on complete collections. To simplify and improve the recovery cycle of potato shoot tips cryopreserved with the droplet-vitrification method, it was assessed if placing shoot tips after thawing for 9 days on culture medium with normal and stable sucrose concentration of 0.073 M (in darkness), can increase the viability rate, compared to a stepwise decrease of the sucrose concentration from 0.3 M to 0.2 M to 0.1M and 0.073 M during the initial phase of the recovery cycle (control treatment). The experiment was performed with 68 diverse potato landraces which showed a significantly higher recovery rate of 69.8 % when shoot tips were recovered on culture medium with a stable sucrose concentration of 0.073 M, compared to the control treatment (57.9 %). The difference in recovery rates was confirmed during routine cryopreservation: a set of 806 accessions recovered with the control treatment showed an average recovery rate of 60.9 % (years 2018-19), while 1158 accessions processed with the new protocol had an average recovery rate of 75.1 % (2019-now). Currently, CIP conserves 4017 virus-free potato accessions in its cryobank, which represent about 83% of the in vitro collection (4851 accessions). Based on a high experimental sample size of 68 tested accessions (1.4 % of population) robust and reliable results about the cryo-response of the whole collection were obtained.